Comparing depositional modes of cave sediments using magnetic anisotropy. (November 2020) - Parés, J.M.; Campaña, I.; Duval, M.; Sier, M.J.; Ortega, A.I.; López, G.I.; Rosell, J.
Abstract: Deciphering the origin and depositional history of archaeological and paleontological deposits is fundamental to evaluate artifact and fossil contextualization. We present new rock magnetic data based on the anisotropy of magnetic susceptibility (AMS) that allow the fabric analysis and characterization of depositional modes in cave sediments. This approach was tested on both fossiliferous and sterile deposits for Gran Dolina and Galeria localities from the Atapuerca karstic complex (Spain). Our AMS approach has allowed to determine paleoenvironmental conditions in both sites, as well as to establish where a given sedimentary unit preserves primary depositional fabrics or has possible post-depositional perturbation. In this sense, it is worth emphasizing that even the sampled horizons that have hominid remains Gran Dolina show no signs of fabric disruption or evidence for massive transport of the sedimentary particles. Highlights: We Decipher the origin and depositional history of archaeological and paleontological deposits. The anisotropy of magnetic susceptibility (AMS) allows fabric analysis and testing possible post-depositional perturbation. The studied stratigraphic units including hominid-bearing layers show no signs of fabric disruption or evidence for massive transport of the sedimentary particles.